2005
DOI: 10.1038/sj.mp.4001685
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor variants are associated with childhood-onset mood disorder: confirmation in a Hungarian sample

Abstract: Brain-derived neurotrophic factor (BDNF) is a nerve growth factor that has been implicated in the neurobiology of depression. Our group has previously reported an association between a BDNF variant and childhood-onset mood disorder (COMD) in an adult sample from Pittsburgh. We hypothesize that variants at the BDNF locus are associated with COMD. Six BDNF polymorphisms were genotyped in 258 trios having juvenile probands with childhood-onset DSM-IV major depressive or dysthymic disorder. Keywords: neurotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 49 publications
4
93
1
1
Order By: Relevance
“…Moreover, the BDNF gene as well as the Val66Met polymorphism have been associated with increased risk for a number of neuropsychiatric disorders (Neves-Pereira et al, 2002;Sklar et al, 2002;Schumacher et al, 2005;Strauss et al, 2005;Okada et al, 2006).…”
Section: Bdnfmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the BDNF gene as well as the Val66Met polymorphism have been associated with increased risk for a number of neuropsychiatric disorders (Neves-Pereira et al, 2002;Sklar et al, 2002;Schumacher et al, 2005;Strauss et al, 2005;Okada et al, 2006).…”
Section: Bdnfmentioning
confidence: 99%
“…In a recent study, Kaufman et al found that children carrying the met allele of the BDNF gene val66met polymorphism and two short alleles (s/s) of 5-HTTLPR had the highest depression scores, but that this vulnerability was only evident in children with maltreatment history (Kaufman et al, 2006). This result is somewhat surprising, because most reports studying the val66met polymorphism have suggested that the met allele is protective for anxiety (Lang et al, 2005;Hunnerkopf et al, 2007) depression (Schumacher et al, 2005;Strauss et al, 2005;Frodl et al, 2007), but see Jiang et al (2005), and bipolar disorder (Neves-Pereira et al, 2002;Sklar et al, 2002). Indeed, in a separate study, the prevalence of depression due to multiple life events was found to be dramatically increased in s/s elders with one met allele (Kim et al, 2007).…”
Section: Genetic Epistasismentioning
confidence: 99%
“…The short allele is generally associated with reduced transporter activity and lower SLC6A4 expression 19 -precisely the functional effect of the SSRIs used to treat depression -although a recent study investigating allelic expression in the serotonin transporter gene found no correlation between expression levels and the promoter polymorphism. 20 Other genes that have been putatively associated with MDD include those encoding tryptophan hydroxylase, 21 brain-derived neurotrophic factor, 22,23 catechol-O-methyl transferase, 24 phospholipase A2, 25 the glucocorticoid receptor 26 and the serotonin receptor 1A, 27 although these findings still await convincing replication in other samples (see Levinson 28 a recent review).…”
mentioning
confidence: 99%
“…Excluded: no MDD phenotype, 8,14,67,68,[85][86][87][88][89][90][91][92][93][94][95][96][97] no case-control design, 22,31,[98][99][100][101][102][103] no adults 104,105 and no Hardy-Weinberg equilibrium (HWE). 106 Included: Caucasian studies, 11,[33][34][35][36][37][38][39][40] Asian studies 19,21,[41][42][43] and gender studies.…”
Section: Meta-regression Analysesmentioning
confidence: 99%
“…29,30 Also, a family-based study showed the Val allele to be associated with childhood-onset mood disorders. 31 Other studies did not observe any association of the Val66Met polymorphism with MDD 11,[32][33][34] (see also Table 1). …”
Section: Introductionmentioning
confidence: 99%